The Influence of Work Motivation and Communication on Employee Performance at the Golden Tulip Jineng Resort Sunset Road Bali Hotel - Nugraha, Surya; Rusmiati, Ni Nyoman (Akademi Komunitas MAPINDO, 2024)
Motivation and Communication have an important role in creating employee performance in a company. This research was conducted foranalyze the influence of work motivation and communication on performance employees at the Golden Tulip Hotel Jineng Resort Sunset Road Bali, This research aims to determine the influence partially and simultaneous between motivation and communication on employee performance, as well to determine the influence of independent variables simultaneously on dependent variable. The total population in this study was 57 people respondents. This research uses quantitative methods. Based on the results analysis shows that the results of the regression analysis show that Motivation has t-calculated value 3.544 > t-table 2.005 and obtained a significant value of 0.001 < 0.05, this can be concluded to mean that motivation has a positive effect and significant impact on employee performance at Golden Tulip Jineng Resort Bali. From the results of the Communication analysis, the t-count value is 4.562> t-table 2.005 and obtained a significance value of 0.00 <0.05, this can be concluded means that communication has a positive and significant effect on Employee Performance at the Golden Tulip Jineng Resort Bali Hotel. By Simultaneity is shown by the F test results where the calculated F value is obtained amounting to 24.869> F-table 3.168 with a significant value of 0.00 < 0.05. so It can be concluded that Motivation and Communication have an influencepositive and significant simultaneously on Employee Performance in Golden Tulip Jineng Resort Bali. Keywords: Motivation, Communication, Employee Performance